Safety and Efficacy of N-SORB®, a Proprietary KD120 MEC Metabolically Activated Enzyme Formulation: A Randomized, Double-Blind, Placebo-Controlled Study. (3rd October 2019) - Wang, Qiurong; Guo, Rui; Nair, Sreejayan; Smith, Derek; Bisha, Bledar; Nair, Anand S.; Nair, Rama; Downs, Bernard W.; Kushner, Steve; Bagchi, Manashi
Abstract: Background: Enzymes are crucial for all aspects of metabolic function. Digestive enzymes from natural sources have been credited with beneficial effects in the digestion and absorption of food. N-SORB is a novel KD120 multienzyme complex (MEC) of metabolically activated enzymes composed of proteases, amylases, lipases, alpha-galactosidase, and glucoamylase from natural sources. These enzymes are encapsulated in a SK713 SLP (non-GMO soy lecithin phospholipid) absorption technology (Prodosome ® ). Objective: This randomized, double-blind placebo-controlled investigation assessed the safety and efficacy of N-SORB KD120 MEC in healthy male and female volunteers on various parameters of the blood, immunity, body composition, physical health, and quality of life following a 90-day intervention. Methods: Forty-six male and female (mean age: 25.8 ± 12.1 years) healthy volunteers were randomly assigned to receive either N-SORB (1 mL, twice daily) or placebo for 90 consecutive days. Complete blood count, as well as blood glucose, liver enzymes, and lipid profile were assessed pre- and post-intervention. Serum cytokine levels were determined by using a Bio-Plex Pro Human Cytokine 8-plex assay and enzyme linked immunosorbent assay (ELISA). Whole body composition analysis was performed by dual-energy x-ray absorptiometry (DEXA) to determine body fat mass, lean mass, and android and gynoid fat. Body weight, blood pressure, and physical health were assessed. Changes in quality of life were examined using the World Health Organization Quality of Life–abbreviated version and sleep quality was assessed using the 24-item Pittsburgh Sleep Quality Index (PSQI) questionnaire. Adverse events were monitored before, during, and after completion of the study. Results: Of the 46 subjects enrolled, a total of 40 subjects successfully completed the study. Compared to placebo, changes in blood cell counts including hematocrit, hemoglobin, mean corpuscular volume, platelets, and lymphocytes provide evidence of some improvement. Quality of life (QOL) parameters showed a small but significant improvement in the N-SORB group. A significant increase was observed in aspartate aminotransferase level in the placebo group at the end of 90 days of treatment; however, no increase was observed in the N-SORB group. No significant changes in blood urea nitrogen, serum creatinine, alkaline phosphatase, alanine aminotransferase, and lipid profile were observed between the placebo and treatment groups before and following intervention. No adverse effects were reported. Conclusions: This randomized, double blind, placebo-controlled clinical study demonstrates that short-term intervention with N-SORB improves the QOL and PSQI in healthy volunteers and did not significantly alter cardiometabolic parameters, lipid profile, or body composition.